HUBUNGAN ANTARA KONDISI SANITASI LINGKUNGAN DAN PERILAKU 3M PLUS PADA KELUARGA TERHADAP KEJADIAN DBD - Suryanti, Lilis; Ardiansyah, Ardiansyah; Arjuna, Arjuna (Ensiklopedia of Journal, 2025)
Dengue Hemorrhagic Fever (DHF) is a disease caused by dengue virus infection and transmitted through the bite of Aedes aegypti and Aedes albopictus mosquitoes. The incidence of DHF is greatly influenced by environmental sanitation conditions and community prevention behavior. An unclean environment and lots of stagnant water are ideal breeding grounds for Aedes mosquitoes, increasing the risk of dengue virus transmission. This study aims to determine the relationship between environmental sanitation conditions and 3M plus behavior in families with the incidence of DHF in the Toboali Health Center Work Area in 2024. This study uses a case control study design. This study was conducted by distributing questionnaires to 54 DHF patients and 54 DHF patients at the Toboali Health Center, South Bangka Regency on October 30 - November 20, 2024. The data collected were then analyzed univariately and bivariately using the chi-square test. The results of this study prove that there is a relationship between environmental sanitation (p-value = 0.000), and 3M plus behavior (p-value = 0.000) on the incidence of DHF in the Toboali Health Center Work Area in 2024. It is hoped that the Toboali Health Center can routinely hold counseling at the RT/RW level, schools, and places of worship to increase public awareness of the importance of 3M Plus behavior. Using visual media such as posters, videos, and direct simulations can strengthen public understanding of preventive measuresKeywords : DBD, 3M Plus Behavior, Environmental Sanitation.